Strengthening teaching practice with Learning Analytics: a case study (2020)
This article shows the analysis and evaluation of a case study about the implementation of the CloudLabs classroom management software, conducted in an educational institution in Bogotá, in the area of natural sciences in sixth to eleventh grades. The objective was to develop the analytical competence in the teachers through a mixed learning environment, InnovalacTIC, for their appropriation of knowledge and skills in the personalization of learning on the basis of the data. From a qualitative methodology, focused on a research-action design, it was possible to recognize the contribution of the Learning Analytics tools and of the CloudLabs virtual laboratory in the personalization of learning and in the formative evaluation. Moreover, the implemented learning environment allowed to define the required teaching competences and, in general, the difficulties that must be overcome for the use of data as a tool for transformation in classrooms.